2021
DOI: 10.1155/2021/4793517
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Radiation‐Induced Brain Necrosis

Abstract: Radiation-induced brain necrosis (RBN) is a serious complication of intracranial as well as skull base tumors after radiotherapy. In the past, due to the lack of effective treatment, radiation brain necrosis was considered to be progressive and irreversible. With better understanding in histopathology and neuroimaging, the occurrence and development of RBN have been gradually clarified, and new treatment methods are constantly emerging. In recent years, some scholars have tried to treat RBN with bevacizumab, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 142 publications
0
13
0
Order By: Relevance
“…Patients with RTLI may suffer long-term headaches, insanity, dizziness, memory loss, personality changes, and seizures ( 32 ). These symptoms may greatly affect the quality of life of patients with NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with RTLI may suffer long-term headaches, insanity, dizziness, memory loss, personality changes, and seizures ( 32 ). These symptoms may greatly affect the quality of life of patients with NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, however, there is no evidence-based guideline yet for the diagnosis and treatment of immune-related intracranial necrosis. Clinically, radiation-induced brain necrosis is more common and there are various treatment strategies, including regular imaging follow-up (close observation for small and asymptomatic lesions), hyperbaric oxygen therapy (HBOT), medications, and surgery ( 25 ). Whether these strategies can be applied to immune-related intracranial necrosis still requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies on the pathogenesis of radiation‐induced cognitive impairment have provided valuable insights, but the specific molecular mechanisms involved remain unclear (Schumacher et al, 2021). Previously, radiation‐induced brain injury was thought to be due to DNA damage (Tofilon & Fike, 2000; Yang et al, 2021), but this theory has been shown to be untenable. Neurogenesis in adults has been shown to play an important role in certain types of hippocampus‐dependent cognitive function (Aimone et al, 2006).…”
Section: Introductionmentioning
confidence: 99%